2012
DOI: 10.1007/s00417-012-1955-2
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized retinal pigment epithelial detachment in age-related macular degeneration: treatment and RPE tear incidence

Abstract: Effective treatment for vascularized PED is still lacking. Until now, only stabilization of the disease has been achieved using anti-VEGF therapy, but the risk of RPE tear can further hamper our expectations. Baseline characteristics are helpful for prognosis, but patients must be informed of the uncertain response. New therapeutic strategies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 38 publications
1
23
1
3
Order By: Relevance
“…However, previous reports have suggested that functional long-term prognosis of PED is generally poor, even under anti-VEGF treatment. 29,34 Some studies have reported an association of vascularized PED with poor functional outcomes; 31,35 while others have found an association between poor functional outcomes and baseline PED height. 30 It is interesting to note that we found a better short-term functional improvement for eyes that presented SRF at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous reports have suggested that functional long-term prognosis of PED is generally poor, even under anti-VEGF treatment. 29,34 Some studies have reported an association of vascularized PED with poor functional outcomes; 31,35 while others have found an association between poor functional outcomes and baseline PED height. 30 It is interesting to note that we found a better short-term functional improvement for eyes that presented SRF at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown variable outcomes associated with anti-VEGF therapy for this condition. 1,[6][7][8][9][10][11][12][13][14][15][16][17][18][19] In 2012, Introini et al 13 studied 132 eyes with vPED or retinal angiomatous proliferation lesions treated with PDT, PDT and intravitreal corticosteroid (IVT),or anti-VEGF therapy over 10 years. At 12 months after treatment, there was marked worsening of vision for eyes treated with PDT or PDT and IVT, and mild decreased vision for eyes treated with anti-VEGF injections despite favorable anatomic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies evaluated the outcomes of ranibizumab for treating vPED due to AMD, but not comparing the results of various doses of ranibizumab. 1,[6][7][8][9][10][11][12][13][14][15][16][17][18][19] Our prospective study addressed the benefits and risks of 2.0 vs 0.5 mg ranibizumab for treating vPED due to AMD on a monthly as well as pro-re nata (PRN) basis for up to 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…RPE tears either appear at the time of admission or occur after the applied treatment modalities. The incidence of RPE tears in PED patients secondary to ARMD is reported in 40% of patients treated with PDT and in 26% of patients treated with anti-VEGF (19) . In the literature, some publications reported a worsening of VA due to the occurrence of an RPE tear after the anti-VEGF injection.…”
Section: Discussionmentioning
confidence: 99%